(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article examines the organization of tourist companies within the dynamic and competitive tourism and hospitality industry. The analysis highlights how global challenges, sustainability imperatives, and digital transformation shape the strategies and structures of modern tourism enterprises. Key determinants include the interaction between supply and demand in the tourism market, the integration of Environmental, Social, and Governance (ESG) principles, the role of Corporate Social Responsibility (CSR) in employee engagement, and the adoption of advanced digital technologies. Special attention is given to the development of Smart Tourism Destinations, which rely on data-driven insights from diverse sources, enabling improved decision-making and tailored services. The study concludes that successful tourist companies must adopt a holistic organizational approach, balancing market competitiveness, sustainability, employee well-being, and technological innovation.